Pattern of intentional drowning mortality: a total population retrospective cohort study in Australia, 2006-2014 - Muthia Cenderadewi; Richard C. Franklin; Amy E. Peden; Sue Devine (BMC, 2019)
Abstract Background While a downward trend in unintentional drowning deaths in Australia has been observed, little is known about intentional drowning mortality. Limited information on intentional drowning death impedes the planning, implementation, and evaluation of prevention strategies. This study aims to describe rates of intentional fatal drowning in Australia and compare these to other categories of drowning. Methods Data were sourced from the Australian Bureau of Statistics (ABS) over a 9-year period (2006-2014). Rates and trends of intentional drowning were compared with unintentional, water-transport related and undetermined intent drowning. Rates of intentional drowning deaths across gender, age groups, states/territories, remoteness of residence and First Peoples of Australia were calculated. Relative risk (RR) (95% confidence interval [CI]) was calculated, and chi-square tests of independence were performed (p < 0.05). Results The crude mortality rate for intentional drowning deaths in Australia over the study period was 0.23/100000, lower than unintentional drowning (0.89/100000). Males were 1.6 (CI: 1.4-2.0) times more likely than females to intentionally drown, however females made up a significantly larger proportion of intentional drowning deaths (38.2%) compared to unintentional deaths (22.4%) (χ2 = 47.3; df = 1; p < 0.05). A significant linear association between age group and intentional drowning was observed (χ2 = 131.3; p < 0.05), with individuals aged 75 years and over 32.6 times more likely to intentionally drown. Non-Indigenous peoples were 4.1 times more likely to intentionally drown in comparison to First Peoples of Australia. Residents of Inner Regional, Outer Regional, and Major Cities were 4.2 times (CI: 0.6-30.0), 4.1 times (CI: 0.6-29.9), and 4.0 times (CI: 0.6-28.6) more likely to intentionally drown, respectively, compared with residents of Very Remote areas. Conclusions This study adds to the limited evidence currently available about intentional drowning rates and trends in Australia. Being male, of older age groups, non-Indigenous, residing in Inner and Outer Regional areas, and Major Cities were risk factors for intentional drowning deaths. Improving data collection systems and furthering understanding of the risk factors of intentional drowning, as well as the development, implementation, and evaluation of prevention programmes, are required to reduce the risk of intentional drowning death in Australia.